Depression screening in adults by pharmacists in the community: a systematic review. (9th August 2020) - Miller, Peter; Newby, David; Walkom, Emily; Schneider, Jennifer; Li, Shu Chuen
Abstract: Background: Improving the identification of depression in adults in primary care can produce clinical and economic benefits. Community Pharmacists may play a role in screening for depression. Objective: To systematically review and evaluate the evidence for the feasibility, impact and cost-effectiveness of community pharmacists screening adults for depression. Methods: An electronic literature search using the databases EMBASE, PubMed and CINAHL Complete from January 2000 to September 2019 was undertaken to identify studies involving community pharmacists screening for depression. Data relating to sample size, population demographics and medical conditions of adults screened were extracted. Details around the screening model, process-related outcomes, clinical outcomes and economic outcomes were also extracted. Results: Ten studies using eight unique depression screening tools were identified. Ease of administration was the most common selection criterion ( n = 4) while no reason was given in four studies. Seven studies reported that through screening, pharmacists could identify adults with undiagnosed depression. Pharmacists referred adults screening positive for assessment in seven studies and followed up participants in two studies. No study assessed the impact of screening on depressive symptoms or the cost-effectiveness of pharmacists screening for depression. Conclusion: Community pharmacists are able to use depression screening tools to identify undiagnosed adults having symptoms of depression. However, there is little evidence around the impact of this screening on clinical and economic outcomes. Larger, well-designed studies that use a highly accurate, easily administered screening tool and include patient referral and follow-up and pharmacist training are warranted to provide evidence on the impact of community pharmacists screening adults for depression.